2021
DOI: 10.3390/biomedicines9101388
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Fluorescence-Guided Surgery for Pediatric Ewing, Osteo-, and Rhabdomyosarcomas: A Literature Review

Abstract: Sarcomas are a rare heterogeneous group of malignant neoplasms of mesenchymal origin which represent approximately 13% of all cancers in pediatric patients. The most prevalent pediatric bone sarcomas are osteosarcoma (OS) and Ewing sarcoma (ES). Rhabdomyosarcoma (RMS) is the most frequently occurring pediatric soft tissue sarcoma. The median age of OS and ES is approximately 17 years, so this disease is also commonly seen in adults while non-pleiomorphic RMS is rare in the adult population. The mainstay of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 127 publications
(132 reference statements)
0
10
0
Order By: Relevance
“…c A literature review discussed the positive and negative aspects of both targeted and nontargeted NIR, suggested targets for common pediatric sarcomas, and outlined the experiments that need to be done before widespread implementation of fluorescenceguided surgery [10].…”
Section: Read This Nextmentioning
confidence: 99%
See 1 more Smart Citation
“…c A literature review discussed the positive and negative aspects of both targeted and nontargeted NIR, suggested targets for common pediatric sarcomas, and outlined the experiments that need to be done before widespread implementation of fluorescenceguided surgery [10].…”
Section: Read This Nextmentioning
confidence: 99%
“…A review summarizing the state of the art in sarcoma margin assessment reported that NIR fluorescence intraoperative imaging may provide surgical benefits in understanding tumor anatomy, perfusion, lymphatic drainage, margins and metastases [1]. A literature review discussed the positive and negative aspects of both targeted and nontargeted NIR, suggested targets for common pediatric sarcomas, and outlined the experiments that need to be done before widespread implementation of fluorescence-guided surgery [10]. A status report about the ongoing randomized controlled trial comparing negative-pressure wound therapy versus conventional wound dressing and associated postoperative wound complications after surgical removal of deep-seated, high-malignant soft tissue sarcoma of the extremities or trunk wall indicated that the results may have implications for all major musculoskeletal resections, including total femur resection [20].…”
Section: Read This Nextmentioning
confidence: 99%
“…Many factors can influence the EPR effect, including tumor type, size, and vascular mediators. As a result, the intensity of the ICG signal is unpredictable ( 20 ). If the patient has a fracture or ischemia at the surgical site during surgery, it will cause false-positive results and affect the judgment.…”
Section: Principle Of Fluorescence Imagingmentioning
confidence: 99%
“…After intravenous administration, ICG binds to serum proteins and appears as macromolecules in the circulation. ICG can passively accumulate in tumor tissue through enhanced permeability and retention (EPR) [ 9 ] and has been used to visualize tumors or sentinel lymph nodes in breast [ 10 ], gastric [ 11 ], lung [ 12 ], liver [ 13 ], and several other types of surgery [ 14 , 15 ]. Recently, some studies have reported the surgical resection of bone and soft tissue sarcomas with ICG-guided near-infrared imaging, which may prove that this technology can be safely used in the treatment of bone and soft tissue tumors [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%